Hypoxia as a barrier to immunotherapy in pancreatic adenocarcinoma - Daniel, S. K. (Clin Transl Med, 2019)
Pancreatic ductal adenocarcinoma (PDA) is a lethal disease with limited response to cytotoxic chemoradiotherapy, as well as newer immunotherapies. The PDA tumor microenvironment contains infiltrating immune cells including cytotoxic T cells; however, there is an overall immunosuppressive milieu. Hypoxia is a known element of the solid tumor microenvironment and may promote tumor survival. Through various mechanisms including, but not limited to, those mediated by HIF-1α, hypoxia also leads to increased tumor proliferation and metabolic changes. Furthermore, epithelial to mesenchymal transition is promoted through several pathways, including NOTCH and c-MET, regulated by hypoxia. Hypoxia-promoted changes also contribute to the immunosuppressive phenotype seen in many different cell types within the microenvironment and thereby may inhibit an effective immune system response to PDA. Pancreatic stellate cells (PSCs) and myofibroblasts appear to contribute to the recruitment of myeloid derived suppressor cells (MDSCs) and B cells in PDA via cytokines increased due to hypoxia. PSCs also increase collagen secretion in response to HIF-1α, which promotes a fibrotic stroma that alters T cell homing and migration. In hypoxic environments, B cells contribute to cytotoxic T cell exhaustion and produce chemokines to attract more immunosuppressive regulatory T cells. MDSCs inhibit T cell metabolism by hoarding key amino acids, modulate T cell homing by cleaving L-selectin, and prevent T cell activation by increasing PD-L1 expression. Immunosuppressive M2 phenotype macrophages promote T cell anergy via increased nitric oxide (NO) and decreased arginine in hypoxia. Increased numbers of regulatory T cells are seen in hypoxia which prevent effector T cell activation through cytokine production and increased CTLA-4. Effective immunotherapy for pancreatic adenocarcinoma and other solid tumors will need to help counteract the immunosuppressive nature of hypoxia-induced changes in the tumor microenvironment. Promising studies will look at combination therapies involving checkpoint inhibitors, chemokine inhibitors, and possible targeting of hypoxia. While no model is perfect, assuring that models incorporate the effects of hypoxia on cancer cells, stromal cells, and effector immune cells will be crucial in developing successful therapies.